Полиномы, порождающие коды Хэмминга - Барашко, А.С. (Український математичний журнал, 1993)
A class of polynomials generating base q Hemming codes (PGHC class) is studied. Criteria for a polynomial to belong to the PGHC class are found in the general case and in the case when the polynomial is prime. Conditions under which reducible polynomials do not belong to the PGHC class are detennined.